Effect of water cooling on microstructure and mechanical properties of friction stir welded dissimilar 2A12/6061 aluminum alloys. (1st May 2022) - Shi, Chao; Sun, Hongwei; Liu, Chao; Zhu, Kaizhen; Yang, Qiulin
Abstract: In-process cooling has been reported beneficial to some friction stir welded (FSW) aluminum alloys. But the effect of water cooling (WC) on the performance of dissimilar joints is still unclear. This work studies the effects of process parameters and water cooling on the microstructure and mechanical properties of the dissimilar 2A12-T6/6061-T6 FSW joints. Two rotational speeds (1200 and 1500 rpm) and one welding speed (80 mm min −1 ) were adopted. The macro/micro structural characteristics, microhardness distribution, tensile properties and fracture morphology have been investigated. The results show 2A12 on advancing side shows the higher plasticizing degree than 6061 during FSW. Cracks and tunnels are found in nugget zone (NZ) of 1200-80WC joint due to the poor fluidity of metals. The average grain size of NZ increases with the rotational speed and can be decreased by water cooling. For all of the joints, the lowest hardness positions locate in the heat affected zone of 6061. The effect of water cooling on hardness is found related to the nature of material and the rotational speed. The 1200-80 joint shows the best mechanical properties. Water cooling damages the mechanical properties of the 1200-80 joint by inducing void and crack defects. However, it enhances the strength of 1500-80 joint. The 1200-80WC joint fractures in NZ while others fracture in the positions with the lowest hardness. The fracture locations and morphology accord well with the microstructure, microhardness and tensile properties.